Ecofy App UX Design using User-Centered Design Approach for Waste Management - Baihaqi, Wiga Maulana; Liulinuha, Qurrota A'yun; Buana, Tresnanda Agsifa Cakra; Najmuddin, Faris Labib (Edu Komputika Journal, 2024)
Indonesia faces a significant waste management challenge, particularly with plastic waste, which poses severe environmental risks and has low recycling rates. This study aims to address these challenges by designing and developing the Ecofy application using the User-Centered Design (UCD) approach. The focus is on creating a solution that not only meets user needs but also effectively facilitates the waste management process, making it more accessible and efficient for the general population. The UCD methodology was employed to ensure that the application’s features are intuitive, user-friendly, and tailored to the local waste bank model, which encourages recycling at the community level. The research involved multiple stages, including user needs assessment, iterative design, and usability testing, to refine the application. The findings demonstrate that the Ecofy application significantly enhances the effectiveness of waste management by offering practical tools for users to sort, manage, and recycle waste. Furthermore, the implementation of this application is projected to reduce the burden on Final Processing Sites (TPA), lower environmental pollution, and increase recycling rates, especially for non-biodegradable materials like plastic. The success of Ecofy could serve as a model for other regions facing similar waste management issues, contributing to broader sustainable development goals in Indonesia.